Implicações da interação genótipo por ambiente e divergência genética das linhagens de soja - Rezende, Daniela Freitas (2009)
Soybean strains selection for high grain yield and adaptation ability to a wide range of environments is one of the major objectives of breeding programs, thus seeking to know better the genotypes in relation to Genotype x Environment interactions. Therefore, this study evaluated the magnitude of the effects of genotype (G), environment (A) and the interaction G x A, quantifying the genetic divergence of the lines studied, using the Average Standardized Euclidian distance, with the Nearest Neighbor method. The experiments are part of the trials for Cultivation Value and Use of the Soybean Breeding Program of Universidade Federal de Uberlândia, and were done on eight counties in the states of Goiás, Mato Grosso, Bahia and Minas Gerais. The experimental design was randomized blocks with three repetitions. Grain yield was evaluated in the harvests of 2006/07 and 2007/08, and the study of genetic divergence was done in the harvest 2007/08, through the variables number of days until maturation, insertion of the first pod, plant lodging, grain yield, weight of one thousand seeds, percentage of oil and protein, yield of oil and protein. The data were submitted to grouped analyses of variances and the averages compared by the Tukey test at 5% probability. The analysis of the interaction G x A was done for the study of genetic divergence. When no significant differences were found, general averages for the strains were used; however, when the interaction was significant, the strains averages by location were used and the dissimilarity of the strains were presented through the distances. The interaction G x A was found for every location analyzed, showing for grain yield the most productive genotypes for each location, together with those that were above the general means. On the trial of semi-early strains, the line UFU-006 had greater yield average in the eight locations evaluated, and was better than the controls, highlighting the great genetic potential, reached in Alto Taquari and Uberaba. On the trial of medium/late cycle strains, the most productive ones on the overall average of the two harvests were UFU-106 and UFU-112, and the control Garantia, which reached the best genetic potential in Alto Taquari and Uberaba. Among the variables evaluated for the divergence study, dissimilarity was found in the semi-early strains for the pairs Emgopa 316 and UFU-006, while UFU-0014 and UFU-0011 were the most similar. The superiority of line UFU-006 guarantees success in the selection and greater magnitude in genetic gains. Maximum divergence found for medium/late cycle strains was for M-Soy 8914 and UFU-109, and the most similar ones were UFU-113 and UFU-107. The strains that were dissimilar consist on good options to obtain segregating populations with high yield, and high oil and protein contents.